Adiaphora: The Israel Folau Case, Heterodoxy and ‘Orthodox Sexual Desire’ in Conservative Australian Christianity - Jennings, Mark A. (Journal for the academic study of religion, 2023)
In April 2019, athlete Isileli ‘Israel’ Folau was sacked for posting anti-LGBTQ+ social media messages. The ‘Israel Folau case’ was contentious in Australia and internationally. Although Folau claimed to be expressing genuinely held Christian beliefs, he has previously articulated heterodox anti-Trinitarian ideas. Throughout Christian history, orthodox beliefs concerning the Trinity have been central. Conversely, same-sex desire has been variously tolerated or censured, but has mostly been regarded as adiaphora: a matter of marginal importance. I argue that the support Folau received from two conservative Christian bodies—the Australian Christian Lobby and the Anglican Diocese of Sydney—suggests that in Australian conservative Christianity, ‘orthodox’ sexuality is now regarded as central, with orthodox belief now de facto consigned to adiaphora.